Development of programming skills through project-based Learning in students of a private university of Lima - Lévano Stella , Miguel Alfredo (2024)
The main objective of this research is to evaluate the influence of project-based learning with the Arduino platform on the development of programming skills of students of the Computer Systems Engineering degree at the Universidad Privada del Norte 2023. The research methodology was framed by a quantitative approach, with a quasi-experimental design. To carry out the field work, the following instruments were used: a survey, an pretest and posttest. The sample was made up of 39 students from the eighth cycle of the Computer Systems Engineering degree who are taking the Robotics course. The main conclusion of the study indicates that Project-Based Learning does significantly influence the development of programming skills of the students of the Robotics course of the computer systems engineering career. This influence becomes evident in the stages of design, implementation, testing and analysis of the operation of the robotic system.